М. О. Гершензон: Неизвестное письмо 1921 года к Б. Л. Модзалевскому [An Unknown Letter from Mikhail Gershenzon to Boris Modzalevsky from 1921] - Salman, Marina (Slavica Revalensia, 2026)
The article is an annotated publication of a previously unknown letter by Mikhail Gershenzon to Boris Modzalevsky from 1921, accidentally found outside the Modzalevsky archival collection at the Institute of Russian Literature (Pushkin House). This newly found letter allows us to understand correctly the previously published letter from Modzalevsky to Gershenzon. The article also contains a critique of the republication of Gershenzon’s memoir about Leo Tolstoy (1960).